Artificial Intelligence and Internet of Things for renewable energy systems - Priyadarshi, Neeraj; Sanjeevikumar, Padmanaban 1978-; Hiran, Kamal Kant; Holm-Nielson, Jens Bo ca. 20./21. Jh; Bansal, Ramesh C. (De Gruyter, 2022)
This book explains the application of Artificial Intelligence and Internet of Things on green energy systems. The design of smart grids and intelligent networks enhances energy efficiency, while the collection of environmental data through sensors and their prediction through machine learning models improve the reliability of green energy systems
Keywords: Energiesysteme; Erneuerbare Energien; Künstliche Intelligenz; Maschinelles Lernen; COMPUTERS / Intelligence (AI) & Semantics; Energieversorgung; Internet der Dinge; Elektrizitätsversorgungsnetz; Intelligentes Stromnetz; Sensortechnik; Aufsatzsammlung